Knowledge, Husband Support, and Culture as the Main Determinants of Timeliness of K1 Visits for Pregnant Women - Abdul Latip; Mariya Ulfah; Doni Yanu Arianto (Knowledge Dynamics, 2025)
Background: K1 is the first contact of pregnant women with health workers who have good clinical/obstetric and interpersonal competence, to get integrated and comprehensive services according to standards. The first contact should be made as early as possible in the first trimester (0-12 weeks). The achievement of K1 visits for pregnant women in Bojonegoro Regency in 2022 was 96.7% of pregnant women. Based on the 2022 Monitoring Report of Maternal Health at the Dander Public Health Center, Bojonegoro Regency, the achievement of Pure K1 Visits for pregnant women is 87.41% of the target of 100%, so that there are 12.59% of pregnant women who are not on time at the first visit. Methods: This observational analytic study employed a cross-sectional design. The sample consisted of 117 pregnant women in their second and third trimesters, selected using simple random sampling. Collecting data using a questionnaire. Data were analyzed using the Multiple Logistic Regression Test to assess influence of knowledge, accessibility, and husband support, and culture on the timeliness of K1 visits with p<0.05. Collecting data using a questionnaire. Results: There was an influence of knowledge (p=0.007), husband support (p=0.017), and culture (p=0.032) on the timeliness of K1 visits. There was no effect of accessibility (p=0.732). Conclusion: Good knowledge of K1 visits will foster awareness and positive attitudes in conducting early pregnancy checks; husband's support can provide motivation, and foster awareness of the importance of early pregnancy checkups; a culture that values and prioritizes the health of the mother and fetus will encourage pregnant women to immediately carry out pregnancy checks early. The researcher is then expected to be able to research other factors that can affect the K1 visit of pregnant women, namely belief, motivation, facilities, community leaders, and health workers.